Big-Five Personality: Prediction of Fear of Missing Out, Problematic Social Media Use, and Deceptive Behavior - Silverius Y. Soeharso; Clara Moningka; Selviana Selviana (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2023)
Very rapid development in information technology, one of which lies in social networking media. The use of social media continued to increase from 2013 (42%) to 2015 (47%). The extensive use of social media causes adverse effects such as deceptive behavior (in social media), constant urge to go online, problematic social media use, and checking social media (fear of missing out). This study examines how Big-Five personality affects deceptive behavior, FoMO, and problematic social media use. The sampling technique used was convenience sampling, which 121 students in DKI Jakarta selected. Multiple linear regression and multivariate multiple regression were used to examine the data. As a result, there is a strong correlation between the Big-Five personality in predicting FoMO, deceptive behavior, and problematic social media use. This finding has implications for universities, especially for lecturers with a background in psychology, to direct and provide knowledge to students to avoid deceptive behavior, problematic social media use, and fear of missing out.